Dialysate White Blood Cell Change after Initial Antibiotic Treatment Represented the Patterns of Response in Peritoneal Dialysis-Related Peritonitis. (30th August 2016) - Tantiyavarong, Pichaya; Traitanon, Opas; Chuengsaman, Piyatida; Patumanond, Jayanton; Tasanarong, Adis
Abstract : Background . Patients with peritoneal dialysis-related peritonitis usually have different responses to initial antibiotic treatment. This study aimed to explore the patterns of response by using the changes of dialysate white blood cell count on the first five days of the initial antibiotic treatment. Materials and Methods . A retrospective cohort study was conducted. All peritoneal dialysis-related peritonitis episodes from January 2014 to December 2015 were reviewed. We categorized the patterns of antibiotic response into 3 groups: early response, delayed response, and failure group. The changes of dialysate white blood cell count for each pattern were determined by multilevel regression analysis. Results . There were 644 episodes in 455 patients: 378 (58.7%) of early response, 122 (18.9%) of delayed response, and 144 (22.3%) of failure episodes. The patterns of early, delayed, and failure groups were represented by the average rate reduction per day of dialysate WBC of 68.4%, 34.0%, and 14.2%, respectively (p value < 0.001 for all comparisons). Conclusion . Three patterns, which were categorized by types of responses, have variable rates of WBC declining. Clinicians should focus on the delayed response and failure patterns in order to make a decision whether to continue medical therapies or to aggressively remove the peritoneal catheter.